Experimental investigation of the aerodynamic drag of roof-mounted insulators for trains. (September 2020) - Tschepe, Jonathan; Maaß, Jörg-Torsten; Nayeri, Christian Navid; Paschereit, Christian Oliver
This paper presents the results of experimental investigations on the aerodynamic drag of roof-mounted insulators for use on low- and high-speed trains. Wind tunnel investigations at different Reynolds numbers in the subcritical, critical, and supercritical flow regime were performed, in addition to investigations using wall-mounted cylinders. Furthermore, the impact of insulator sheds made of flexible material was analyzed. For a better understanding of the aerodynamic behavior of the insulators when mounted on trains, different boundary conditions representing realistic configurations as found on the roof of trains were simulated. From the measured drag, the energy demand to overcome the aerodynamic resistance of different types of insulators was calculated. Depending on the above mentioned boundary conditions, a noticeable contribution of the insulators to the entire train's aerodynamic drag could be observed. With flexible insulator sheds, a further increased air resistance was observed with the onset of fluttering. Similar to the cylinder, the aerodynamic behavior of the insulators depends on the respective Reynolds number.